Original paperAssessment of interleukin-18 concentration in patients with stable and unstable angina pectoris and with type 2 diabetes mellitus - Prokopczuk, Przemysław; Krętowski, Adam; Wawrusiewicz-Kurylonek, Natalia; Poniatowski, Bogusław; Gugała, Kamil; Bachórzewska-Gajewska, Hanna; Kochman, Wacław; Okruszko, Anna; Górska, Maria; Kinalska, Ida (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2007)
Aim: To assess concentration of interleukin-18 (IL-18) in patients with stable and unstable angina pectoris and with type 2 diabetes mellitus. Material and methods: The study was conducted in a cohort of 584 patients, randomly selected from 4655 patients after coronarography. Study group patients were divided into 4 subgroups: patients with coronary artery disease (CAD) and diabetes (DM), with CAD but without DM, with DM but without CAD, and without CAD or DM. The control group consisted of apparently healthy, unrelated, randomly selected volunteer subjects, inhabitants of the Podlasie region (n=204). In 237 patients after coronarography, chosen at random from all the study subgroups, and in 40 individuals from the control group serum concentration of IL-18 was assessed. Results: A trend for higher concentration of IL-18 in subgroups with diabetes was observed. IL-18 concentration was the highest in patients with unstable angina pectoris, significantly higher than in patients without CAD symptoms, both in patients with diabetes and without carbohydrate disturbances (p<0.04). IL-18 concentration was significantly higher in patients with 3-vessel disease in coronarography in comparison to patients with single vessel disease (353.3±105.8 vs. 299.3±86.3 pg/ml, p=0.035). A statistically significant correlation between IL-18 concentration and WHI (p=0,46) as well as total cholesterol (p=0.0075) and LDL cholesterol (p=0.007) was observed. Conclusions: 1. Results of the presented study confirm the correlation between IL-18 concentration and occurrence of angina pectoris both in patients with diabetes mellitus and without carbohydrate disturbances. 2. A positive correlation between IL-18 concentration and extent of atherosclerosis in coronarography was observed in the presented group of patients. 3. Elevated IL-18 concentration found in diabetic patients, correlating with metabolic syndrome clinical features and level of LDL cholesterol, may suggest existence of an additional mechanism augmenting the risk of CAD in patients with diabetes and carbohydrate disturbances.